Effect of different interset rest intervals on mean velocity during the squat and bench press exercises - González-Hernández, Jorge M; Jimenez-Reyes, Pedro; Janicijevic, Danica; Tufano, James J; Marquez, Gonzalo; Garcia-Ramos, Amador (Sports biomechanics, 2023)
This study aimed to compare the effect of three interset rest intervals (1, 3, and 5 minutes) on (I) mean velocity during a resistance training session conducted in a Smith machine with the squat and bench press exercises, and (II) the pre- and post-exercise force-velocity relationship. Fifteen male university students completed three sessions (i.e., Rest 1', Rest 3', and Rest 5') consisting of three sets of five repetitions against the 10RM load during the squat and bench press exercises. The force-velocity relationship (maximal values of force [F0], velocity [v0], and power [Pmax]) was evaluated at the beginning and at the end of each session with the countermovement jump and bench press throw exercises. During training, mean velocity was slower in sets 2 and 3 of the Rest 1' protocol compared to Rest 3' and Rest 5', but no significant differences were present between Rest 3' and Rest 5'. After training, there was a significant decrease in F0 (p = 0.017) and Pmax (p = 0.010), but not in v0 (p = 0.259). These results support the Rest 3' as the most time-efficient protocol, among those analysed, for the maintenance of high mean velocities during training sessions not leading to failure.
Keywords: svalová síla; Resistance Training; Humans; linear position transducer; Weight Lifting; strength training; lidé; vzpírání; odporový trénink; Muscle Strength; kosterní svaly; velocity-based training; Male; Muscle, Skeletal; Exercise; biomechanika; mužské pohlaví; cvičení; Biomechanical Phenomena; Force-velocity relationship